PTU-007 Improving documentation after paracentesis – optimising patient safety with good record keeping. (17th June 2017) - Hessey, S; Payne, A; Than, NN; Patch, D
Abstract : Introduction: Paracentesis is frequently performed by trainee doctors. The procedure is associated with significant complications including bleeding and viscera perforation, hence comprehensive documentation is essential. Good record keeping facilitates better communication between staff and, consequently, improves patient care. We aimed to assess the quality of paracentesis documentation at the Royal Free Hospital and improve areas identified as suboptimal in order to maximise patient safety. Method: A total of 21 documentation components were identified as essential for safe ascitic drain insertion, management and removal based on current British Society of Gastroenterology guidelines and expert opinion. We reviewed the case notes of 50 patients who underwent paracentesis over a 5 month period. Results: We divided the 20 essential documentation components into three parts: 9 documentation points for drain insertion, 5 instructions for drain management and 6 documentation points for drain removal. We found that 100% of paracentesis procedures were documented in black ink in the correct section of the case notes and all entries included record of verbal consent. Otherwise there was a large variation in the quality of documentation with an average of 52% (n=29) compliance with the essential documentation components. In particular, explanation of procedure-associated complications, pre-procedure INR and platelet count results, time of drain removal, total volume drained and volume of albumin administered, were poorly recorded. In order to encourage better compliance with the essential documentation components, we designed a poster for the doctor's office. No improvement was detected as a result of this intervention. We therefore designed a sticker to facilitate clear record keeping of the essential components after paracentesis. Introduction of the sticker resulted in an immediate and sustained increase in documentation compliance to 81% (n=14). The greatest improvement was seen in regard to recording details of the procedure (100%, n=14) and post-procedure care instructions (100%, n=14). Conclusion: Following introduction of the sticker, overall documentation improved dramatically within days and was sustained over subsequent weeks. Using a pre-designed sticker also helps to educate trainees about procedural complications and management of patients following ascitic drain insertion. Disclosure of Interest: None Declared